Effect of Oral Oxymetholone on lean body mass and Insulin resistance in End-Stage renal disease patients on maintenance Hemodialysis - Nattida Kobpipat (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2006